A Nilai Multikultural: Jalan Perdamaian Melampaui Dialog Antar Agama - folandra Folandra (Jurnal SUARGA: Studi Keberagamaan dan Keberagaman, 2023)
The many issues of conflict in the name of religion have attracted the attention of leaders towards peace. Efforts offered such as inter-religious dialogue tend to be carried out after a conflict occurs. This article aims to offer an attitude of diversity through an understanding of multicultural values ​​as a way of peace before interfaith dialogue. This article uses a qualitative study in the form of a literature study. Data is collected through journals, books as well as other manuscripts that are considered to enrich the study. This study finds that peace efforts have been carried out by world leaders through interfaith dialogue. However, this dialogue tends to be in the realm of courtesy and prevents mere offense. Therefore, it is necessary to understand multicultural values ​​as an effort that becomes the attitude of each individual human being. This value must be instilled from an early age, such as respecting and accepting differences, and seeing the basic principles of equality as a unifying bond. Multicultural values ​​also inculcate to oppose forms of oppression, discrimination, war, and other crimes.